In vivo organization of the FtsZ‐ring by ZapA and ZapB revealed by quantitative super‐resolution microscopy. Issue 6 (14th August 2013) - Buss, Jackson; Coltharp, Carla; Huang, Tao; Pohlmeyer, Chris; Wang, Shih‐Chin; Hatem, Christine; Xiao, Jie
Summary In most bacterial cells, cell division is dependent on the polymerization of the FtsZ protein to form a ring‐like structure (Z‐ring) at the midcell. Despite its essential role, the molecular architecture of the Z‐ring remains elusive. In this work we examine the roles of two FtsZ‐associated proteins, ZapA and ZapB, in the assembly dynamics and structure of the Z‐ring in Escherichia coli cells. In cells deleted of zapA or zapB, we observed abnormal septa and highly dynamic FtsZ structures. While details of these FtsZ structures are difficult to discern under conventional fluorescence microscopy, single‐molecule‐based super‐resolution imaging method Photoactivated Localization Microscopy (PALM) reveals that these FtsZ structures arise from disordered arrangements of FtsZ clusters. Quantitative analysis finds these clusters are larger and comprise more molecules than a single FtsZ protofilament, and likely represent a distinct polymeric species that is inherent to the assembly pathway of the Z‐ring. Furthermore, we find these clusters are not due to the loss of ZapB–MatP interaction in ΔzapA and ΔzapB cells. Our results suggest that the main function of ZapA and ZapB in vivo may not be to promote the association of individual protofilaments but to align FtsZ clusters that consist of multiple FtsZ protofilaments.